Eksplorasi Dampak Electronic Word of Mouth Terhadap Perilaku Pembelian Konsumen di Toko Online Shopee - Fadhillah, Wanda; Subali, Subali (Gorontalo State University, 2025)
Consumer behavior in online stores is influenced by several factors such as reviews from other users. These reviews greatly affect the attractiveness of online stores and consequently show an impact on consumer purchasing behavior. This study intends to show the impact of electronic word of mouth on consumer purchasing behavior in the Shopee online store. This study uses a quantitative research method with a sample of 100 respondents using a purposive sampling method. Data were collected using questionnaire distribution techniques and simple linear regression analysis. This study shows the results that E-WOM has a significant impact on customer purchasing behavior, by obtaining a calculated t value (2.896) t table (1.960) and a significance t test (0.005) 0.05, then H0 is rejected and H1 is accepted. Thus, E-WOM shows its influence on consumer purchasing behavior in the Shopee online store by 79%.